[EMIm][BH3CN] Ionic Liquid as an Efficient Catalyst for the Microwave- Assisted One-Pot Synthesis of Triaryl Imidazole Derivatives - Manjul, Rajesh K.; Gaikwad, Suresh T.; Gade, Vilas B.; Rajbhoj, Anjali S.; Jopale, Manohar K.; Patil, Shripad M.; Gaikwad, Dhananjay N.; Suryavanshi, Dayanand M.; Goskulwad, Santosh P.; Shinde, Suvarna D. (Letters in Organic Chemistry, 2023)
In this present investigation, efficient and general protocols for the synthesis of a series of imidazoles 4(a-p) derivatives have been developed by cyclocondensation of aromatic aldehydes, benzil and ammonium acetate in the existence of efficient [EMIm][BH3CN] ionic liquid catalyst under microwave condition in good to excellent yields (91-97%). The structures of the synthesized compounds have been confirmed by IR and NMR spectra. The significant features of this protocol are an uncomplicated workup process, rate enhancement with high yields, and efficient catalysts. It was concluded that [EMIm][BH3CN] is the finest catalyst under MW heating conditions.
Keywords: MW irradiation